PENGARUH BESARAN PERUSAHAAN, FINANCIAL LEVERAGEDAN NET PROFIT MARGIN (NPM) TERHADAP PRAKTIK PERATAAN LABA (INCOME SMOOTHING) PADA PERUSAHAAN INDUSTRI DASAR DAN KIMIA DI BURSA EFEK INDONESIA - Bunga Maharani (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2012)
The aim of this study isto examine the influence of company’s characteristics toward income smoothing practice among listed basic and chemical companies at Indonesia Stock Exchange. The factors being examined were size of the company, company’s financial leverage ratios, and company’s net profit margin ratios. Index Eckel is used to determine the income smoothing practice. The object of income smoothing in this study is the net profit of the company. The study was using 61 basic and chemical companies listed in Indonesia Stock Exchange, with a period between 2003-2005. The hypothesis was tested using Multiple Linier Regression. Both t-test and F-test have also been used to test the significance of the study hypothesis. The result of this study showed that some of basic and chemical companies listed at Indonesia Stock Exchange were committed to income smoothing practice. Multiple Linier Regression showed that both partially and simultaneously, size of the company, company’s financial leverage ratios, and company’s net profit margin ratios didn’t prove to have a significant influence on income smoothing. Keywords: size of the company, financial leverage, net profit margin, income smoothing